Exact solutions by integrals of the non-stationary elliptic Calogero–Sutherland equation. Issue 1 (24th February 2020) - Atai, Farrokh; Langmann, Edwin
Abstract: We use generalized kernel functions to construct explicit solutions by integrals of the non-stationary Schrödinger equation for the Hamiltonian of the elliptic Calogero–Sutherland model (also known as elliptic Knizhnik–Zamolodchikov–Bernard equation). Our solutions provide integral representations of elliptic generalizations of the Jack polynomials.